Investigation of the production parameters, nutrient and mineral composition of mealworm (Tenebrio molitor) larvae grown on different substrates - Molnár, Áron; Toviho Odunayo Abigeal; Milán Fehér (Acta Agraria Debreceniensis, 2022)
During the rearing of mealworm (Tenebrio molitor) larvae, the optimisation of the growing substrate has a particular importance. The application of the appropriate substrate is a fundamental pillar for intensive and safe production. The requirements for substrate include the lack of toxins, high nutrient and micro-macro element content. The aim of this study was the evaluation of the effects of different substrates on the production parameters, nutrient and mineral composition of the mealworm larvae. The experiment lasted through 14 days. 5 treatments were set up at, where the variable was the substrate. The test system consisted of 25 units (5 treatments and 5 replicates). 10 mealworm larvae per unit, (total of 250 larvae) were used at the beginning of the experiment. Regarding the substrates, our study included sweet potato (SP), may turnip tuber (MT) and may turnip leaf (ML). In addition to the plant by-products, wheat flour (WF) and wheat semolina (WS) were used as control substrates. Trace element uptake and production parameters of the larvae were determined at the end of the experiment. Regarding the production parameters, it can be stated that the wheat semolina (0.081 ± 0.005 g) and wheat flour (0.069 ± 0.007 g) substrate used as control gave the best results for the final body weight. In terms of plant raw materials and by-products, sweet potatoes (0.063 ± 0.007) can only be recommended as substrate, while may turnip tuber and may turnip leaf produced significantly lower final body weight results (MT=0.034 ± 0.002 g ; ML= 0.036 ± 0.002 g). The nutrient composition of the larvae was not affected by the substrate, these results confirmed the high protein and fat content reported in the literature. The results with the production parameters were contradicted by the micronutrient content. Larvae reared on may turnip leaf (ML) and tuber (MT) showed the highest values for most of the macro- and microelements (potassium, calcium, magnesium, iron, zinc, copper) tested.